2016
DOI: 10.1016/j.canlet.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Scinderin promotes the invasion and metastasis of gastric cancer cells and predicts the outcome of patients

Abstract: Invasion and metastasis are major malignant characteristics of human gastric cancer (GC), but the underlying molecular mechanisms are poorly understood. Recent studies have shown that scinderin (SCIN), an actin severing and capping protein that regulates the actin cytoskeleton, is involved in the proliferation and migration of certain cancer cells. Accordingly, this study aimed to investigate the potential role of SCIN in the invasion and metastasis of human GC cells and to evaluate its prognostic value for GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…A wound-healing assay was performed to examine the capability of cancer cell migration, as previously described 40 . Briefly, GC cells were grown in 24-well plates with RPMI-1640 medium supplemented with 10% FBS up to 90% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wound-healing assay was performed to examine the capability of cancer cell migration, as previously described 40 . Briefly, GC cells were grown in 24-well plates with RPMI-1640 medium supplemented with 10% FBS up to 90% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Invasion assay was performed as previously described 40 . Briefly, GC cells were seeded in the upper chamber (8 μm, 24-well format) coated with 10 μL of matrigel (BD, USA)/RPMI-1640 (1:1, v/v) at 2 × 104 cells/well in 200 μL RPMI-1640 medium without FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al 21 found that CAPZA1 is a marker for a good prognosis in GC and is associated with the decreased migration and invasion of cancer cells. Liu et al 47 reported that Scinderin inhibited the formation of filopodia and decreased the expression of CDC42 along with GC cell migration. Srivatsan et al 48 further indicated that knockdown of CD2AP in plasma cell‐like dendritic cells resulted in migration defects, and Zhao et al 49 found that CD2AP functions synergistically to enhance the function of cortactin, which enhances branched actin filament formation and promotes cell spreading and migration in mice podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel transwell analyses were performed as previously described (13 agonist and antagonist and signaling inhibitors on the invasiveness of GC cells, the metrigel-transwell system were cultured with or without ML133 (20 µM, TOCRIS) or Zacopride (10 µM, Sigma-Aldrich) or PD98059 (10 µM, Selleck) or LY3009120 (20 µM, Selleck). After incubation for 24 h at 37°C, the invasive cells were stained with 1% crystal violet and then counted from five random visual areas under a microscope.…”
Section: In Vitro Gc Cell Invasion Assaymentioning
confidence: 99%
“…Immunoblot analyses were performed as previously described (13). GC cells were washed twice with ice-cold PBS then lysed with protein extraction reagent (Thermo, USA) containing 1% protease inhibitors (Thermo, USA).…”
Section: Western Blotmentioning
confidence: 99%